DC and AC conductivity of chitosan-silver triflate polymer electrolyte - Aziz, S.B.; Rusli, M.S.; Abidin, Zul Hazrin Zainal; Arof, Abdul Kariem (2009)
T~e frequency and temperature dependence of to DC and AC conductivity of chitosan-silver tnflate electrolyte has been studied from 303 K to 423 K and over a frequency range of 50 Hz to 1000 ~Hz. The conductivity was found to increase with the increase in AgCF3S03 concentration. The DC conductivity increases in the low temperature region but decreases at high r temperatures. From the total conductivity versus frequency plots dispersion from DC to AC conductivity can be observed below 358 K.